Comparing Assessments of Physical Functional Independence in Older Adults With Mobility Limitations. (August 2019) - Mortenson, W. Ben; Fuhrer, Marcus J.; Bilkey, Jessica; Jutai, Jeffrey; Alkadri, Jamal; Aziz, Joseph; Demers, Louise
Abstract : Objectives: The aims of the study were (1) to assess the agreement and correlation between self-reported functional independence and observations of family caregivers in a heterogeneous population of community-dwelling older adults with disabilities and (2) to determine how self-reports and caregiver reports correlate with evaluator rated functional independence over time. Design: Data were drawn from a larger, randomized controlled trial examining the effects of a caregiver-inclusive intervention on outcomes of care recipients and their family caregivers. Functional independence measures were obtained using a self-report version of the Functional Independence Measure (care recipient self-reported Functional Independence Measure, caregiver self-reported Functional Independence Measure) and the Functional Autonomy Measurement System (evaluator perspective). They were administered at baseline (preintervention) and after the intervention at 6, 22, and 58 wks. Results: Bivariate correlation analyses of 90 dyads consisting of older care recipients and their family caregivers reported moderate to very strong correlations between the three functional independence measures across all time points ( r S = 0.45–0.91, P < 0.01). Bland-Altman analyses revealed a small systematic bias between care recipient and caregiver assessments of functional independence, with participants reporting higher scores across all time points (mean difference = 2.00–2.97). Conclusions: There is substantial consistency among the self-assessed, caregiver-assessed, and evaluator assessed functional independence of older adults. Caregivers may be used as proxies for community-dwelling older adults without severe cognitive impairments with functional limitations. To Claim CME Credits: Complete the self-assessment activity and evaluation online at http://www.physiatry.org/JournalCME CME Objectives: After reviewing this article, readers will be able to: (1) Describe the strength of association between self-reported functional independence and observations of family caregivers in a heterogeneous population of community-dwelling older adults with disabilities over time; (2) Describe the level of agreement between self-reported functional independence and observations of family caregivers over time; and (3) Describe the associations among self-reported, caregiver reported and evaluator rated functional independence over time. Level: Advanced Accreditation: The Association of Academic Physiatrists is accredited by the Accreditation Council for Continuing Medical Education to provide continuing medical education for physicians. The Association of Academic Physiatrists designates this Journal-based CME activity for a maximum of 1.0 AMA PRA Category 1 Credit(s) ™. Physicians should only claim credit commensurate with the extent of their participation in the activity.